GLOBAL HEALTH CRISIS: FINDING THE IMPERATIVE SOLUTIONS - Shikhin Garg (European Scientific Journal, ESJ, 2015)
The earth is currently the only known planet that is sure to sustain life, with no other heavenly body seeming feasible. We, the humans have been oblivious to this fact and carried out activities that have slowly created a situation that has left us staring at a future which poses issues that are detrimental to the sustainability of our own species. Various human acts have affected in ways that are not intelligible to the community. Although, the realisation started long ago, the measures definitely demand a constant scrutiny to make sure that they are well-equipped to stem the decline to an extent that recovery becomes possible. This paper attempts to gauge the enormity of the situation of health deterioration around the world and identify the causes for it. A discussion of the current initiatives has been done and the measures that require change have been identified based on how they have been faring. Suggestions, in the form of improved solutions based on the need of the hour and with a specific aim of human health improvement have been presented in a bid to utilise the slim possibility of a reversal of states.